Lipoma Removal Surgery in White-Rumped Shama (Kittacincla malabarica macraoura) - Rickyawan, Nofan; Hardian, Andreas Bandang; Cadiwirya, Pradhana Kurniawan (Jurnal Medik Veteriner, 2021)
Lipoma in birds is a benign tumor of adipose cells that often occurs in the subcutaneous area. White-rumped shama, more than three years old, was rushed to the puskesmas with symptoms of decreased activity and singing ability. The results of the examination were two round, multi-focal masses, firmly demarcated, yellowish in color with a soft, chewy consistency measuring ± 4 x 2 x 1 cm on the chest and ± 1 x 1 x 1 cm. in the abdominal area, firmly attached to the subcutaneous layer since six months ago, and getting bigger. The feathers around the mass are shed and vascularized on the surface of the mass. Surgery was performed because the mass suspected of being a tumor growing rapidly and causing pain. It was fasted two hours before surgery and the anesthetic used was a combination of ketamine HCl and xylazine. Postoperative therapy using the antibiotic enrofloxacin, ketoprofen analgesics, 0.9% NaCl fluid therapy and topical antibiotic gentamicin ointment. The tumor that has been successfully removed is yellowish in color with several areas of hyperemia and an oily surface. The results of histopathological examination characterized by the presence of adipose cells that appeared to proliferate well confirmed that the tumor was a lipoma.